OSTEOPOROSIS AND PHYSICAL ACTIVITY IN ELDERLY (Fiep Bulletin - online, 2011)
During the development of the individual's body, the body goes through personal, dynamic and progressive transformations. In the normal aging process, called senescence, are found morphological, functional, biochemical and psychological changes common to elderly individuals. Being the most common change in bone tissue is the loss of its mineral density, osteoporosis. Knowing that physical activity often helps minimize the physiological changes caused by aging, this study aimed, through a literature review, identifying the main bouts of the bone structure of the elderly and physical activity can help reduce or prevent these bone changes developed age. It was observed, therefore, that in specialized literature, regular exercises minimize and prevent loss of bone mineral density by means of compressive forces in which the bone is subjected during physical activity.
Keywords: osteoporosis; bone; physical activity; elderly; senescence